(untitled) (Innovative professional education, 2023)
The socio-pedagogical aspects of youth entrepreneurship counseling are considered. It was determined that its purpose is the formation of entrepreneurial competence in students of professional (vocational and technical) education institutions. The main approaches to pedagogical modeling are considered. The main characteristics of the structural and functional model of youth entrepreneurship counseling are disclosed.